Social Media Ethics Perspective Fiqh Muhammadiyah Information (Instagram Content Analysis of Islamic Broadcasting Communication Program Students at Muhammadiyah University of Mataram) - Hasrullah, Hasrullah; Fathurrijal, Fathurrijal; Ishanan, Ishanan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research is focused on social media ethics of students of the Islamic Communication and Broadcasting Study Program, Faculty of Islamic Religion (KPI FAI Study Program), University of Muhammadiyah Mataram as Instagram users. This study aims to find out how social media ethics and the application of Muhammadiyah Information Fiqh on the content of the Instagram account of KPI study program students. This research uses a descriptive qualitative method, data collection is obtained through observation, interviews, documentation. The research found that the content in the form of photos, videos and text narratives on the Instagram account of the Islamic Communication and Broadcasting Student FAI University of Muhammadiyah Mataram did not violate the code of ethics contained in the Muhammadiyah Information Fiqh. The values and norms contained in the Muhammadiyah information Fiqh have been applied in social media by all 20 KPI FAI students who use Instagram.